Variation in the erythrocyte size among larvae, juveniles and adults of "Hypsiboas cordobae" (Anura, Hylidae) - Baraquet, Mariana (2013)
We aimed at determining sizes and shape of erythrocytes and evaluating the differences among larva, juvenile and adult Hypsiboas cordobae. Length and width of 40 randomly chosen erythrocytes and their respective nuclei from individuals of different ages collected in the experimental field “Las Guindas” (Córdoba, Argentina) were measured. Erythrocyte and nuclear areas were estimated assuming an ellipsoidal shape, and the aspect ratio, which reflects the shape of the cell, was calculated. The erythrocytes were oval, and their nuclei were also oval and centrally located. Erythrocyte size increased with age, whereas nuclei were larger in tadpoles than in juveniles. The cell and nucleus shapes also changed with age from the spherical shape in larvae to the more ellipsoidal one in adults. Discriminant analysis confirmed the existence of highly significant (P < 0.0001) differences in erythrocyte and nuclear areas among larvae, juveniles and adults, with a classification rate of 93.33%.